2021
DOI: 10.1101/2021.11.04.21265908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and immunogenicity of heterologous and homologous inactivated and adenoviral-vectored COVID-19 vaccines in healthy adults

Abstract: In light of intermittent supply shortages of individual vaccines and evidence of rare but serious adverse events after vaccination, heterologous regimens for COVID-19 vaccines have gained significant interest. This study aims to assess the reactogenicity and immunogenicity of the heterologous adenoviral vector vaccine regimen (ChAdOx1-S, AstraZeneca; hereafter referred to as AZ) and the inactivated vaccine regimen (CoronaVac; hereafter referred to as CV) regimen in healthy Thai adults immunized between June an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Additionally, the antibody response after a booster with intramuscular BNT162b2 in our current study (3821 BAU/mL) was similar to previous studies (3884 BAU/mL) [27]. Previous studies have also shown that the mix and match of the platform, namely CV/AZD1222, significantly elicited IgG anti-RBD at 28 days compared to CV/CV [28]. Furthermore, AZD1222/BNT162b synergistically promoted IgG anti-spike at both 28 days [29] and 73 days [30].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the antibody response after a booster with intramuscular BNT162b2 in our current study (3821 BAU/mL) was similar to previous studies (3884 BAU/mL) [27]. Previous studies have also shown that the mix and match of the platform, namely CV/AZD1222, significantly elicited IgG anti-RBD at 28 days compared to CV/CV [28]. Furthermore, AZD1222/BNT162b synergistically promoted IgG anti-spike at both 28 days [29] and 73 days [30].…”
Section: Discussionsupporting
confidence: 89%
“…, and the heterologous boosters with superiority of mRNA 13,14,76-78 over AV 79 have shown to be more immunogenic than homologous boosters in healthy people receiving inactivated priming regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The AE symptoms in previously infected individuals after vaccination were similar to those in individuals without prior infection. Therefore, pre-existing immunity after natural infection may not affect AE symptoms 49,50,51 . Additionally, AEs were more frequent after vaccination with the vector-based vaccine than with the inactivated vaccine, suggesting that different types of vaccines cause different types of local and systemic reactogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Participants received a second dose of CoronaVac 28 d after the first dose and that of AZD1222 8 to 10 weeks after priming. For comparison as reference groups, data on 180 infection-naïve individuals who had been vaccinated with two doses of CoronaVac (n = 90) or AZD1222 (n = 90) were obtained from a previous study 50 . All participants have written consent.…”
Section: Study Design and Participantsmentioning
confidence: 99%